A közigazgatási térszervezési teleszkóp és területszervezési reformviták Romániában az ország európai uniós csatlakozása (2007) óta - Hajdú, Zoltán (Közép-Európai Közlemények, 2014)
Territorial administrative reform is an evergreen theme in the modern history of Romania. This short paper focuses on the processes of regional reform in Romania. Forming new regions (administrative, development) is runing between very complex political environment. The article is investigating political developments from the Romania’s accession to the EU (2007). There are different aims of Roman majority and Hungarian minoriry in this processes. Political parties and society are diveded in the basic questions of reforms. There is a special fear between ethnic Hungarians living in Romania from regional reform plans. The study is analising different theoretical elements (specially administrative organisation telecope), taking some critical thoughts regarding regional reform plans in Romania.